The new rules of marketing & PR : how to use social media, online video, mobile applications, blogs, news releases, and viral marketing to reach buyers directly - Scott, David Meerman (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
"The pioneering guide to the future of marketing, The New Rules of Marketing & PR, has been updated and revised to retain its place as the top marketing and public relations book available. Learn the latest tools and techniques to communicate with buyers directly and in real-time, raise online visibility, and increase sales. For professionals, entrepreneurs, business owners, and professors alike, this one-of-a-kind guide offers actionable strategies that can be implemented immediately. In this completely revised and updated Fifth edition, David Meerman Scott offers fresh examples of success from organizations around the world ; delivers revised and expanded information on techniques like Inbound Marketing, Content Marketing, and Newsjacking; and offers the latest on social networks such as YouTube, Twitter, Facebook, Instagram, Snapchat, and LinkedIn. The New Rules of Marketing & PR gives you the inside track to gain attention for your product, service, or idea at a fraction of the cost of traditional marketing and PR programs." -- Back cover.
Foreword / Robert Scoble -- Introduction -- I. How the web has changed the rules of marketing and PR : -- The old rules of marketing and PR are ineffective in an online world -- The new rules of marketing and PR -- Reaching your buyers directly -- II. Web-based communications to reach buyers directly : -- Social media and your targeted audience -- Blogs: tapping millions of Evangelists to tell your story -- Audio and video drive action -- Going viral: the web helps audiences catch the fever -- The content-rich website -- Marketing and PR in real time -- III. Action plan for harnessing the power of the new rules : -- You are what you publish: building your marketing and PR plan -- Growing your business: how marketing and PR drive sales -- Online thought leadership to brand your organization as a trusted resource -- How to write for your buyers -- Mobile marketing: reaching buyers wherever they are -- Social networking as marketing -- Blogging to reach your buyers -- An image is worth a thousand words -- Video and podcasting made, well, as easy as possible -- How to use news releases to reach buyers directly -- Your newsroom: a front door for much more than the media -- The new rules for reaching the media -- Newsjacking your way into the media -- Search engine marketing -- Make it happen.
Index included.
Keywords: Internet marketing; Public relations